(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Mobile ad hoc network is a wireless network group of mobile devices having no infrastructure. Load balancing is an important problem in such networks due to dynamic topology of the nodes. Many protocols are developed to improve the bandwidth, energy efficiency and throughput of these networks. With the increasing use of MANETs they are evolving wit use of applications and for non- uniform load distribution it’s difficult to manage the load. Load balancing provides a single internet service from multiple servers as a commonly used application. Multicasting support at the link layer is essential for the efficient use of network resources. system propose a light weight dynamic channel allocation scheme for MANET. The system compares two algorithms DCA -TRACE and CMH-T RACE to provide support for non-uniform load distributions and propose CDCA-TRACE. It increases the number of source nodes and reduce the number of collisions, energy consumptions and average absolute IPDV drastically.